Macroeconomic indicators and CO₂ emissions in the EU region - Nestor Shpak; Solomiya Ohinok; Ihor Kulyniak; Wodzimierz Sroka; Armenia Androniceanu (Amfiteatru Economic Journal, 2022)
The anthropogenic emissions of carbon dioxide into the atmosphere are one of the problems facing mankind on a global scale. Therefore, the governments of many countries are making efforts to reduce CO2 emissions through regulatory measures. Environmental pollution from CO2 emissions is not only an environmental problem, but also an economic one. Therefore, the authors focus on conducting a multi-econometric study of the impact of macroeconomic factors (gross domestic product, exports, imports, inflation, and unemployment) on CO2 emissions in the EU region. Systematization, empirical comparative analysis, and econometric modeling (determining the relationships between indicators) were the research methods applied in our research. The results, which were carried out based on statistical data for the period 1970-2020 in the EU, confirmed the existence of dependence of carbon dioxide emissions on macroeconomic indicators such as gross domestic product, exports, imports, inflation, and unemployment. To know whether to reduce or maintain allowable CO2 emissions, governments can use multivariate regression models to optimize, monitor, and forecast their macroeconomic indicators.
Keywords: C01; E01; E24; E31; F18; O13; Q51; Q53; 330; carbon dioxide; EU; exports; greenhouse gases; gross domestic product; imports; inflation; unemployment